2017
DOI: 10.1515/sdj-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of XP-endo SHAPER (XPS) in cleaning the apical third of the root canal

Abstract: Introduction The aim of this study was to evaluate the efficacy of new rotary NiTi instrument XP endo SHAPER (XPS) used with conventional irrigation protocol on the root canal cleaning in the apical area. Material and methods The research was conducted in vitro on 40 extracted single-rooted teeth divided into the four groups. Instrumentation in the first group was performed using iRa Ce NiTi rotary instruments, in the second group the same instruments were used plus XP endo FINISHER (XPF) for smear layer remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…This is in accordance with the findings of other authors who have showed that increasing the number of irrigation cycles increases the cleaning capacity as the amount of fresh solution is restored, while in the case of continuous irrigation, the saturation of the solution occurs faster [7, 11, 25, 26,]. Živković et al [25] have determined that the protocol of the final irrigation in three cycles improves the efficacy of removing the smear layer in the apex segment of the root canal, and Macedo et al [26] showed that the irrigation protocol in three cycles of fresh NaOCl solution increases its cumulative effect and thus the efficacy of cleaning root canal walls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in accordance with the findings of other authors who have showed that increasing the number of irrigation cycles increases the cleaning capacity as the amount of fresh solution is restored, while in the case of continuous irrigation, the saturation of the solution occurs faster [7, 11, 25, 26,]. Živković et al [25] have determined that the protocol of the final irrigation in three cycles improves the efficacy of removing the smear layer in the apex segment of the root canal, and Macedo et al [26] showed that the irrigation protocol in three cycles of fresh NaOCl solution increases its cumulative effect and thus the efficacy of cleaning root canal walls.…”
Section: Discussionsupporting
confidence: 91%
“…The worst cleaning of dentinal walls in both groups is observed in the apical third of the root canal, then in the middle, while the smallest amount of the smear layer is noticed in the coronal third of both groups, which is in compliance with the results of other studies confirming that the smear layer from the canal walls is more easily removed from the coronal and middle third [9,10,21,26]. The cleansing problem is particularly emphasized in the region of the apical third due to anatomical specificity (isthmuses, ramification, additional canals), and due to the small diameter of the apical preparation, which makes the debridement of the canal more difficult [3,5,7,25].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Diameter of the apical preparation formed in this way allows the tip of the needle to easily reach the apical terminus, which also improves the efficiency of the irrigant in the removal of the smear layer 2,9 . One of the problems of such deep application of irrigation needles in clinical conditions can be the conveyance of irrigant (NaOCl) into periapex, which can cause adverse effects on periapical structures 26 .…”
Section: Discussionmentioning
confidence: 99%
“…12 This finding of XP endo shaper disagrees with other studies such as Živković S. et al, in 2017 and Al-khazali and Salim in 2018 that showed in their results best-centering ability of this file when compared with other instruments. 27,28 In this study the centering ability of XP endo shaper is less than Edge Evolve may be because the file has "snake" shaper, superelasticity and extreme flexibility these properties when combined with continuous rotation at very high speed "800-1000 rpm" and minimal torque may cause the file not to remain in the center of the canal during instrumentation, and finally, the deviation from the center of the canal instrumented by XP endo shaper may be related to six cutting edges at the tip called (booster tips) which enable it to start shaping after a glide path of at least ISO 15, and to gradually increase its working field to achieve an ISO 30. 11 In this study the result of Hyflex CM disagrees with study done by Burklein et al, 2014 and Perez, 2015 which showed better centering ability of Hyflex CM compared with other files, this disagreement may be because the canals instrumented in these studies were "S" shaped and the taperness of other files was larger than Hyflex CM.…”
Section: Discussionmentioning
confidence: 99%